Respostas

2014-03-15T13:13:00-03:00
√396- √108+ √ 176 + √675 
E=√396- √108+ √ 176 + √675 
Fatorando 396,encontramos 
2 * 2 * 3 * 3 * 11 
ou seja, 
2².3².11 
Ficará portanto assim nossa raiz: 
2.3√11 
6√11 (√396) 
Agora vamos fazer com √108: 
√108 
fatorando,encontramos 2².3².3: 
2.3√3 
6√3(√108) 
---------------------------- 
6√11+6√3+ 
Raiz de 176: 
√176=2².2².11 => 2.2√11 => 4√11 # 
Logo,montando a expressão,teremos: 
6√11+6√3+4√11+ 
decompondo 675,temos: 
675|3 
225|3 
75|3 
25|5 
5|5 

3².5².3 
3.5√3 => 15√3 # 
6√11-6√3+4√11+15√3 
Ou seja, 
6√11+4√11-6√3+15√3 
10√11+9√3<----------------------- resposta 
--------------------------- 
4 4 4
2014-03-15T13:17:53-03:00
2.32.3 \sqrt{x} 112.3 \sqrt{x} 32.2 \sqrt{x} 113.5 \sqrt{x} 3 =
 \sqrt{x} 11 - 6  \sqrt{x} 3 +4 \sqrt{x} 11 + 15  \sqrt{x} 3 
10 \sqrt{x} 11+ 9 \sqrt{x} 3
1 5 1